2002
DOI: 10.1089/152308602760598963
|View full text |Cite
|
Sign up to set email alerts
|

Redox Signaling of Angiogenesis

Abstract: Reactive oxygen species (ROS) play a crucial role in vascular angiogenesis. Both in vitro and in vivo studies indicate that angiogenic response in vascular tissue is triggered by ROS signaling in a highly coordinated manner. It appears that massive amounts of ROS produced during ischemia and reperfusion in the vascular tissue, especially in heart, cause significant injury to the cardiomyocyte and endothelial cells. However, during the reperfusion, the same ROS potentiates a repair process and triggers a signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
195
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(202 citation statements)
references
References 88 publications
4
195
0
3
Order By: Relevance
“…However, here we demonstrated that changing the media could also cause fluctuations in DO levels; for instance, media replacement after 24 h reoxygenated the cells, which was previously shown to have crucial effects on cellular responses, including angiogenesis (30,47). Previous studies have reported the values of V max and K m of HUVECs at various cell-seeding densities (15,42).…”
Section: C435 Oscillations In Dissolved Oxygen During Tubulogenesismentioning
confidence: 51%
“…However, here we demonstrated that changing the media could also cause fluctuations in DO levels; for instance, media replacement after 24 h reoxygenated the cells, which was previously shown to have crucial effects on cellular responses, including angiogenesis (30,47). Previous studies have reported the values of V max and K m of HUVECs at various cell-seeding densities (15,42).…”
Section: C435 Oscillations In Dissolved Oxygen During Tubulogenesismentioning
confidence: 51%
“…Additionally, transcription of several gene classes, including cytokines, matrix proteins and hormones, are modulated by NO regulation of nuclear factor ÎșB (NFÎșB), hypoxia inducible factor 1 (HIF1) and zinc-finger transcription factors (Huang et al, 1999b;Kroncke and Carlberg, 2000;Matthews et al, 1996;Tabuchi et al, 1996;Torres and Forman, 2000). ROS, however, regulates transcription of protein kinases, growth factors and transcription factors, and plays a role in signaling in the vasculature (Burdon, 1996;Giaccia and Kastan, 1998;Maulik, 2002;Meyer et al, 1994;Nose, 2000). Additionally, ROS inhibits low molecular weight (LMW) phosphatases, which have been shown to downregulate proliferation by attenuating growth factor receptor signaling (Chiarugi, 2001;Huang et al, 1999a).…”
Section: Discussionmentioning
confidence: 99%
“…Both VEGF and eNOS are up-regulated in situations of increased oxidative stress [51,52]. Therefore, one hypothesis for the observed effects of B vitamins in this study may be through the modulation of oxidative stress following the induction of ischemia.…”
Section: Discussionmentioning
confidence: 63%